Thoracic ultrasonic narration of Covid-19 pneumonia. (2020) - Hegarty, Mairead; Harvey, Gavin; Kearney, Eimhear; Burns, James; Wray, Maria; Gibson, Eddie; Kelly, Rory; Scott, Kate; Masih, Izhaq
Abstract: Covid-19 (SARS-CoV-2) is a new coronavirus. Since the declaration of a global pandemic, a lot has been learnt about its spread, disease pattern, diagnosis and management. The lungs remain the prime organs to incur serious insult and when lung complications embark, significant morbidity and mortality is observed. Predominantly, patchy and peripheral lung distribution in the Covid-19 pneumonia has been described in the radiology experience and literature. There are a range of imaging modes useable in diagnosis, prognosis, monitoring, and therapy of Covid-19. However, when it comes to the appropriateness and the potential benefits of imaging, resource utilization and infectious risk must be considered. The use of ultrasound during this pandemic has provided us with an alternate imaging modality that is easily performed at the bedside, with real time images available to the clinician. This case highlights the role played by the thoracic ultrasound in the diagnosis and progression of Covid-19 pneumonia.